Modelo matemático para simulação de transporte e dispersão de poluentes em rios: aplicação ao estudo de lançamento acidental no Rio Paraíba do Sul - Büge, Tania Regina (1990)
This thesis consists in a finite difference Formulation for solution of the one-dimensional Advection-diffusion equation, with an upstream approximation of the advective term using the QUICKEST (Quadratic Upstream Interpolation for Convective Kinematics with Estimated Streaming Terms ) scheme. For problems in which adjective transport is significant, finite difference solutions employing traditional schemes present numerical problems of oscillation and smoothing of the wave front. The present study shows the better behavior of the QUICKEST algorithm for computing the transport and dillution of pollutants, compared with results obtained with other formulations. Several types of" effluents with different chemical reaction terms are analyzed, and their accidental discharge simulated based on field data obtained from studies carried out in the Paraíba do Sul river. The model developed has shown to be efficient and can be easily implemented in microcomputers.